Utilization of Digital Marketing to Increase the Competitive Advantage of MSMEs in Sentul Village, Babakan Madang District, Bogor Regency - Muhamad Nurfaozi; Eka Rahmawati; Rio Maulana; Alfina Damayanti; Gita Rahmawati; Chandra Ayu Pramestidewi; Samsuri; Titiek Tjahja Andari (Jurnal Pengabdian Masyarakat Formosa, 2023)
Digital transformation impacts all aspects, including online marketing. Students in a community service initiative have identified economic challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Sentul Village, Bogor Regency, related to their limited understanding of digital marketing. To address this, the students propose a program that focuses on enhancing the MSMEs' digital marketing competence, aiming to improve sales efficiency, increase revenue, and expand market reach. The implementation method is descriptive, and the participating MSMEs, Adok Furniture and Tahu Babakan, will receive tailored training and support in digital marketing.